دور ممارسات إدارة الشراء في تحسين الأداء المؤسسي: دراسة تطبيقية على شركات الأدوية في مصر - المرسى، جمال الدين محمد; سليمان، لمياء عبدالرحيم عبدالكريم Suleiman, Lamia Abdulrahim Abdulkarim (جامعة المنوفية - كلية التجارة, 2019)
يستهدف البحث التعرف على دور ممارسات إدارة الشراء في تحسين الأداء المؤسسي بالتطبيق علي شركات الأدوية في مصر، وتوصل البحث إلي مجموعة من النتائج تمثلت في وجود قصور واضح لدي مسئولي إدارة الشراء في تقييم أداء إدارة الشراء، ووجد اختلاف بين ممارسات إدارة الشراء الممتازة و بين ممارسات إدارة الشراء الفعلية وبين مستوي الأداء المؤسسي في شركات الأدوية طبقا لاختلاف نمط الملكية (قطاع الأعمال العام–القطاع الخاص-الشركات متعددة الجنسية)، كذلك وجد اختلاف بين ممارسات إدارة الشراء الفعلية والممتازة، وأخيرا تم التوصل إلي وجود علاقة طردية بين ممارسات إدارة الشراء الفعلية والأداء المؤسسي.
This research aims to identify the role of purchasing department practices in improving the organizational performance in the pharmaceutical companies in Egypt. The findings of the study were as follows: Purchasing managers lack the capability of pursuing an efficient performance evaluation of the purchasing department practices. There are significant differences among the views of purchasing managers about excellent purchasing department practices according to the differences in ownership style. There are significant differences among purchasing practices actually performed in pharmaceutical corporations according to the difference of ownership style There is a significant difference between actual purchasing practices and excellent purchasing practices in pharmaceutical corporations according to purchasing managers' perception as the results show negative variances for most of these dimensions. There are significant differences among the pharmaceutical corporations in terms of organizational performance according to the difference in ownership style. There is a significant positive relationship between actual purchasing practices and the overall organizational performance.
Keywords: مصر -- شركات الأدوية -- إدارة المشتريات -- الأداء الموسسي